Psychological Factors Influencing Healthy Food Consumption Behavior in Adolescents: A Systematic Literature Review - Ziyadi Ali Ikromi; Farah Fadilah Hasyim; Samuel Givency (Eudaimonia Journal Psychology, 2026)
Healthy eating behavior in adolescents is a crucial factor in supporting growth, development, and long-term health. However, various studies have shown that healthy eating behavior is influenced not only by environmental factors and nutritional knowledge but also by psychological factors. Therefore, a comprehensive study is needed to identify psychological factors that influence healthy eating behavior in adolescents. This study aims to identify and analyze psychological factors that influence healthy eating behavior in adolescents through a systematic literature review approach. The study used PRISMA guidelines and analyzed 11 articles published between 2021 and 2026. Data were analyzed through a synthesis process of the psychological factors found in each study. The results of the study indicate that psychological factors influencing healthy eating behavior in adolescents include attitudes, self-efficacy, self-control, motivation, intentions, and subjective well-being. Attitude is the most dominant factor, followed by self-efficacy, self-control, and motivation. Healthy eating behavior in adolescents is influenced by various psychological factors, especially attitudes, self-efficacy, self-control, and motivation. These findings demonstrate the importance of considering psychological aspects in efforts to improve healthy eating patterns in adolescents.